Sosialisasi Ekonomi Dan Perbankan Syariah Di Kota Dan Kabupaten Bogor - Misno (Lembaga Penelitan dan Pengabdian Masyarakat Institut Agama Islam Sahid, 2022)
The Islamic economy and banking that have developed in Indonesia have not been well socialized. This is evidenced by various studies that show the low level of economic literacy and Islamic banking in Indonesia. This fact also occurs in the City and Regency of Bogor, where the results of the study show that Islamic economic and banking literacy is still low in these two areas. Referring to this fact, there is a need for socialization in the community as a form of increasing literacy in the field of economics and sharia banking. This community service program aims to socialize and provide explanations to the public about sharia economics and banking in the City and Regency of Bogor. The activity was carried out using the lecture, explanation and discussion method which was carried out six times in the City and Regency of Bogor with the main focus being on explaining the economy and Islamic banking. The results of this service show an increase in the level of participants' understanding of the economy and Islamic banking, especially those who take this activity seriously